The Relationship between Task Characteristics and Employee Engagement - George, Rowena; Jonathan, Victoria; Michael, Florianna Lendai (UNIMAS Publisher, 2020)
The objective of this study is to identify the relationship between task characteristics (variety of skills, task identity, task significance, autonomy, feedback) and employee engagement. The study was conducted in a healthcare service in Sabah. A self administered questionnaire was used to collect data by using convenience sampling. A total of 78 respondents participated in the study. Data was analyzed using Spearman Correlation. The results revealed a significant and positive relationship between task characteristics (variety of skills, task identity, task significance, autonomy, feedback) and employee engagement in the studied organization. This has important implications to employers. It is recommended that managers, HRD practitioners and supervisors employees with more challenging tasks, autonomy and feedback from time to time. Moreover, work designs should include how the tasks may improve employee identity and significance.